Notas - autor, Sin (Revista General de Información y Documentación, 2004)
Although the publishing house in Spain has been studied on various occasions and from different points of view, one misses a study of Editorial Documentation and the organization of this documentation in specific Centres (Centres of Editorial Documentation - CDE) committed to the conservation and spreading of the documents resulting from editorial activity. A proposal is made regarding the structure of a CDE and a minimal document typology to serve as a reference in order to satisfy these needs.
Keywords: Documentation; Editorial Documentation; Edition; Editorial Management; Document typology